High-Speed Rail & Air Transport Competition - Nicole Adler; Chris Nash; Eric Pels (Tinbergen Institute, 2008)
This paper develops a methodology to assess transport infrastructure investments and their effects on a Nash equilibria taking into account competition between multiple privatized transport operator types. The operators, including high-speed rail, hub and spoke legacy airlines and low cost carriers, maximize profit functions via prices, frequency and train/plane sizes, given infrastructure provision and costs and environmental charges. The methodology is subsequently applied to all 27 European Union countries, specifically analyzing four of the prioritized Trans-European Networks.
Keywords: R40; L92; L93; 330; airlines; high-speed rail; networks; applied game theory; infrastructure pricing; Verkehrsträgerwettbewerb; Luftverkehrsgesellschaft; Hochgeschwindigkeitsverkehr; Netzregulierung; Infrastrukturinvestition; Verkehrstarif; Spieltheorie; Nash-Gleichgewicht; EU-Staaten